1993
DOI: 10.1055/s-2008-1071545
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hemiplegia: Morphology of Cerebral Lesions and Pathogenetic Aspects from MRI

Abstract: We have analyzed the MRI findings from the brains of 33 children with congenital hemiplegia. Referral of these children to our hospital was either because of neurological problems or a history of complicated birth. According to maturation-dependent pathophysiological mechanisms we have classified the lesions into the following five groups: 1. malformations/prenatal encephalo-clastic lesions, 2. periventricular leukomalacia or atrophy, 3. diencephalic lesions, 4. subcortical and cortical lesions, and 5. normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
7

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 4 publications
2
40
0
7
Order By: Relevance
“…Other authors have reported on mixed lesions, though without evaluating clinical impairments. 5,24 Results for sensory modalities were less consistent than for motor outcome. In our study, no differences in sensory function were found between main groups, except for exteroception.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Other authors have reported on mixed lesions, though without evaluating clinical impairments. 5,24 Results for sensory modalities were less consistent than for motor outcome. In our study, no differences in sensory function were found between main groups, except for exteroception.…”
Section: Discussionmentioning
confidence: 86%
“…A similar large proportion of bilateral lesions in hemiplegic children with periventricular lesions was reported by others. 5,8,11 A prominent finding was the significantly better motor performance of children in the PVL-group compared to both …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…27 Although CP is commonly described as a motor impairment, radiological evidence of structural pathology beyond the motor area is common, and bilateral CNS lesions occur in a significant proportion of children with hemiplegic CP. 28,29 It has also been demonstrated that a significant proportion of children show functional impairment in the non-affected hand 30 and, in comparison with healthy age-matched controls, 31 this is associated with bilateral parenchymal lesions on magnetic resonance imaging. 30 It is possible that the extent of the cerebral pathology in hemiplegia could affect process skill ability.…”
Section: Discussionmentioning
confidence: 99%